Hubungan Konsumsi Buah Pepaya dengan Kejadian Konstipasi pada Ibu Hamil di Puskesmas Rumbai Pesisir Pekanbaru - Ardhiyanti, Yulrina (Jurnal Martenity and Neonatal, 2017)
Constipation is a difficult condition or unable to defecate. It has been estimated that approximately 13% to 38%women during their pregnancy experience constipation, especially in earlyand third trimester of pregnancy. More than 2,5 million Indonesian have frequent complaints of constipation, whose prevalence reaches2%. It is estimated that constipation cause 2,5 million patients go to the doctor each year. The cases of pregnant women who suffered from constipation in Puskesmas Rumbai Pesisir about 4 – 30%. This research was conducted to know the Consumption of Papaya Fruit with Constipation in Pregnant Women at Puskesmas Rumbai Pesisir Pekanbaru in 2017. This research is a quantitative research with quasi experimental research design. The number of samples were 15 mothers who had severe constipation as a case and 15 mothers who had mild constipation as control. For cases, sampling procedure done by total population andfor control, using Systematic Random Sampling technique. Data was collected using observation sheets and data analysis was done by univariate and bivariate with T test. The result showed that there was no influence between pretest and postest with constipation in pregnant women without consumption of papaya (OR 0,001; 95% CI 4,47 – 1,99), pretest and posttest with constipation in pregnant mother with consumption of papaya (OR 0,008; 95% CI 4,80 – 2,21). Puskesmas Rumbai Pesisir as the leading health facility in public health service is expected to improve health service especially for pregnant women that requires handling so it can reduce the number of morbidity and anxiety.